2015
DOI: 10.1111/ajad.12288
|View full text |Cite
|
Sign up to set email alerts
|

Treatment outcomes in opioid dependent patients with different buprenorphine/naloxone induction dosing patterns and trajectories

Abstract: Background and Objectives Induction is a crucial period of opioid addiction treatment. This study aimed to identify buprenorphine/naloxone (BUP) induction patterns and examine their association with outcomes (opioid use, retention, and related adverse events [AEs]). Methods The secondary analysis of a study of opioid-dependent adults seeking treatment in eight treatment settings included 740 participants inducted on BUP with flexible dosing. Results Latent class analysis models detected six distinctive ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 24 publications
0
25
0
Order By: Relevance
“…The majority of patients in this study fell into the moderate range of withdrawal, which is consistent with other studies using pharmacotherapy as initial treatment. (9,10,15) A recent study that compared treatment outcomes in opioid-dependent patients with different buprenorphine/naloxone induction doses found that baseline COWS scores influence treatment retention rates. (8) A different study that investigated predictors of outcomes using methadone and buprenorphine therapy concluded that higher withdrawal scores are associated with poorer retention.…”
Section: Discussionmentioning
confidence: 99%
“…The majority of patients in this study fell into the moderate range of withdrawal, which is consistent with other studies using pharmacotherapy as initial treatment. (9,10,15) A recent study that compared treatment outcomes in opioid-dependent patients with different buprenorphine/naloxone induction doses found that baseline COWS scores influence treatment retention rates. (8) A different study that investigated predictors of outcomes using methadone and buprenorphine therapy concluded that higher withdrawal scores are associated with poorer retention.…”
Section: Discussionmentioning
confidence: 99%
“…That doses of 16 mg and higher may be associated with lower drop-out during the induction phase has been shown in analyses of outcome trajectories from the START clinical trial in the US [40,50]. Interestingly, in this study the statistically significant difference in retention for patients treated with 16 mg BUP versus <16 mg BUP was found only for drop-out during the first 28 days, and not for drop out during the later stage of the trial [50]. The importance of a dose of 16 mg daily SL BUP or higher Opioid negaƟve samples (%)…”
Section: Discussionmentioning
confidence: 88%
“…In addition, approximately 24% of patients withdrew during the 7-14 day SL BUP run-in period in a trial of an extended-release BUP formulation [7]. That doses of 16 mg and higher may be associated with lower drop-out during the induction phase has been shown in analyses of outcome trajectories from the START clinical trial in the US [40,50]. Interestingly, in this study the statistically significant difference in retention for patients treated with 16 mg BUP versus <16 mg BUP was found only for drop-out during the first 28 days, and not for drop out during the later stage of the trial [50].…”
Section: Discussionmentioning
confidence: 97%
“…It is possible that the patient could have been stabilised on a lower dose of buprenorphine/naloxone if more time had been given before further titrating her dose, given the long half‐life of buprenorphine. However, recent research has demonstrated that higher initial starting doses of buprenorphine are helpful in improving retention in treatment and decreasing illicit substance use . Ultimately, dosing buprenorphine/naloxone at high doses should proceed with caution given concerns for sedation and other side effects.…”
Section: Discussionmentioning
confidence: 99%